In-Bed Sensorimotor Rehabilitation in Early and Late Subacute Stroke Using a Wearable Elbow Robot: A Pilot Study - Huang, Mei Zhen; Yoon, Yong-Soon; Yang, Jisu; Yang, Chung-Yong; Zhang, Li-Qun (Frontiers in Human Neuroscience, 2021)
Objects: To evaluate the feasibility and effectiveness of in-bed wearable elbow robot training for motor recovery in patients with early and late subacute stroke. Methods: Eleven in-patient stroke survivors (men/women: 7/4, age: 50.7±10.6 years, post-stroke duration: 2.6±1.9 months received 15 sessions of training over about 4 weeks of hospital stay. During each hourly training, participants received passive stretching and active movement training with motivating games using a wearable elbow rehabilitation robot. Isometric maximum muscle strength (MVC) of elbow flexors and extensors was evaluated using the robot at the beginning and end of each training session. Clinical measures including Fugl-Meyer Upper Extremity motor scale (FMA-UE), Motricity Index for upper extremities scale (MI), Modified Ashworth Scale (MAS) were measured at baseline, after the 4-week training program, and at a one-month follow-up. The muscle strength recovery curve overtime was characterized as a logarithmic learning curve with 3 parameters. Results: At the baseline, participants had moderate to severe upper limb motor impairment (FMA-UE (median [interquartile range]): 28 [18-45]) and mild spasticity in elbow flexors (MAS (median [interquartile range]): 0 [0-1]). After about 4 weeks of training, significant improvements were observed in FMA-UE (p=0.003) and MI (p=0.005), and the improvements were sustained at the follow-up. The elbow flexors MVC significantly increased by 1.93Nm (95%CI: 0.93-2.93Nm, p=0.017), the elbow extensor MVC increased by 0.68Nm (95%CI: -0.05-1.98Nm, p=0.036). Muscle strength recovery curve showed that patients with severe upper limb motor impairment had a greater improvement rate in elbow flexor strength than those with moderate motor impairment. Conclusion: In-bed wearable elbow robotic rehabilitation is feasible and effective in improving biomechanical and clinical outcomes for early and late subacute stroke in-patients. Results from the pilot study suggested that patients with severe motor impairment may benefit more from the robot training compared to those with moderate impairment.